The Relation Between Levels of TNF Alpha, IL-1B, PGE2 and PLA with the Severity Degree of Dengue Hemorrhagic - . PURWATI; . NASRONUDIN; ENDANG RETNOWATI KUSUMOWIDAGDO; FEDIK ABDUL RANTAM (Microbiology Indonesia, 2011)
The pathogenesis of dengue virus infection is still being debated.  Based on the existing data, there is a strong evidence that the immunopathological mechanism plays a role in dengue virus infection with various complications.  Some unknown immune responses play a role in the pathogenesis of dengue virus infection. Researchers are trying to establish the role of several inflammatory mediators such as PLA2, IL-1, TNF-, PGE2, PGI2, Thromboxane A2, Leucotrien and MPTP, in relation to the severity degree of the dengue virus infection.  The aim of this study is to recognize the relation between the severity degrees of DHF (Dengue Hemorrhagic Fever) patients and the immunological profile in the sub-cellular level, such as PLA2, IL-1, TNF-, PGE2 and PLA 2.  The collected data was processed and presented analytically. The relation between each parameter (TNFα, SPLA2, PGE2,IL-1β) and the degree of DHF was analyzes, using Spearman's correlation analysis, ordinal regression, and using ANOVA.  It was shown that there was no relation between the levels of TNF-ά, PGE2, IL-1β, and SPLA2  in patients with various degrees of DHF, but there were significant differences between DHF grade 1 and 3, and also 2 and 3, on IL-1β.  There were increased levels of the four parameters in dengue grade 1 to 2, but decreased levels in grade 3. This can be caused by inflammatory processes, but the severity degree of DHF can also be influenced by complement, thromboxane, and leukotrien.